HUBUNGAN DUKUNGAN KELUARGA TERHADAP MOTIVASI PASIEN KANKER PAYUDARA YANG TELAH KEMOTERAPI - Titik Rusmiati; Lisda Maria (Jurnal Kesehatan dan Pembangunan, 2023)
Background: Breast cancer is a malignant cell that can kill the number two woman in the world. Chemotherapy treatment for breast cancer can cause bad side effects so that patient compliance is low. High motivation is needed to be able to comply. One of the motivations is obtained from family support. Objective: to determine the relationship between family support and motivation of breast cancer patients who have received chemotherapy at the Pusri Hospital in Palembang. Methods: This type of research is quantitative observational analytic with a cross-sectional approach. The population in this study were 102 breast cancer patients who underwent chemotherapy at the Pusri Hospital in Palembang. The number of samples is 50 people. This research was conducted in March - April 2022. The data collection used primary data. Data analysis used the Spearman rank test. Results: Most respondents received sufficient family support, namely 56. Most respondents had sufficient chemotherapy motivation, namely 82. There was a relationship between family support and motivation for breast cancer patients to undergo chemotherapy at Pusri Hospital Palembang (P value 0.000). The Correlation Coefficient value of 0.591 which means the strength of the relationship is medium Conclusion: There is a Medium relationship between family support and the motivation of breast cancer patients to undergo chemotherapy at the Pusri Hospital Palembang. Suggestion: to develop intervention research to increase family support in order to motivate cancer patients to undergo breast cancer chemotherapy.